The Birth of Pragmatic Solidarity in Spain: Contesting Centuries of Power and Distance - Bermejo , Víctor Lara (Jordan Journal of Modern Languages & Literatures, 2023)
The use of informal pronouns of address in virtually any context in current Spain is a trend that has been related to the establishment of democracy. However, latest research points out that the fashion for solidarity commenced more than two hundred years ago. In this paper, I aim to account for the opinions and attitudes of the 18th- and 19th-century Spanish press in order to find the geographical and social origins of this fact, as well as the reaction of the different media, based on their prevailing ideology. The results show that the tendency towards solidarity comes from France and is promoted by the upper urban class, though it is vehemently contested by the conservative spectrum of society.